College students' perceived benefit-to-risk tradeoffs for nonmedical use of prescription stimulants: Implications for intervention designs. (April 2018) - Ross, Melissa M.; Arria, Amelia M.; Brown, Jessica P.; Mullins, C. Daniel; Schiffman, Jason; Simoni-Wastila, Linda; dosReis, Susan
Abstract: Objectives: Few studies have examined the benefit-to-risk tradeoffs undergraduate students perceive when engaging in the nonmedical use of prescription stimulants (NPS). This study examined the variation in college students' perceived risks and benefits for NPS. Methods: An online survey was administered to 259 college students (ages 18–25) at six public universities who had engaged in NPS in the past year. A best-worst scaling (BWS) instrument assessed the relative importance of 12 perceived benefits and risks of NPS. Probabilities of selection of each factor and 95% confidence intervals were estimated for the aggregate sample and latent preference subgroups were derived using latent class analysis (LCA). Results: For the aggregate sample, the strongest motivators for NPS were better grades (m = 2.33, p < 0.05) and meeting deadlines (m = 1.62, p < 0.05). The LCA generated four subgroups: 1) assuredly performance-driven (n = 64; 25%), who prioritized academic performance and nonacademic responsibilities; 2) cautiously grade/career-oriented (n = 117; 45%), who balanced academic improvements with expulsion and limiting future career opportunities; 3) risk-averse (n = 64; 25%), who prioritized expulsion above academic improvements; and 4) recreational (n = 14; 5%), who most valued having fun partying. Conclusions: These findings identify subgroups of college NPS users that could have vastly different trajectories in terms of future drug use and college performance. Given this heterogeneity among students regarding perceived risks and benefits of NPS, interventions should be designed to assess motives and provide personalized feedback. Further research is needed with larger, more diverse samples and to assess the prospective stability of perceived risks and benefits. Highlights: College students make tradeoffs for nonmedical stimulant use heterogeneously. On aggregate, students prioritize perceived academic benefits over risks. However, subgroups nonmedically use stimulants despite being risk-averse. A small subgroup of students prioritizes recreational use above other motives. We recommend interventions assess motives and provide individualized feedback.